2018
DOI: 10.1002/jcp.27388
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to target energy metabolism in consensus molecular subtype 3 along with Kirsten rat sarcoma viral oncogene homolog mutations for colorectal cancer therapy

Abstract: Alterations in cellular energy metabolism play a critical role in colorectal cancer (CRC), which has been identified as the definition of consensus molecular subtypes (CMSs), and CMS3 tumors exhibit energy metabolism signatures along with Kirsten rat sarcoma viral oncogene homolog (KRAS)-activating mutations. This review summarizes the relationship between CMS3 tumors associated with mutated KRAS and energy metabolism in CRC, especially for the dysregulated energy metabolism that affects tumor cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…We have previously described an energy metabolism network link between KRAS-mutant CRC and multiple metabolic pathways, including lipids, amino acids, FA metabolism and glycolysis, and several factors and metabolic genes, such as alanine, serine, cysteine-preferring transporter 2, stearoyl-CoA desaturase (SCD), FASN, ACSL, c-Myc, glutaminase-1, ATP-binding cassette subfamily A member 1, glucose transporter 1, asparagine synthetase and 1-acylglycerol-3-phosphate O-acyltransferase 1. These factors induce metabolic changes and regulate metabolic pathways together with major energy sources associated with mutant KRAS, and they are often overexpressed in CRC patients with poor prognosis ( 38 ). ACSL1 is involved in lipid synthesis, modification and β-oxidation; and SCD is the main enzyme controlling the rate of conversion of saturated FA to monounsaturated FA ( 39 ), which is crucial for cancer cells ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described an energy metabolism network link between KRAS-mutant CRC and multiple metabolic pathways, including lipids, amino acids, FA metabolism and glycolysis, and several factors and metabolic genes, such as alanine, serine, cysteine-preferring transporter 2, stearoyl-CoA desaturase (SCD), FASN, ACSL, c-Myc, glutaminase-1, ATP-binding cassette subfamily A member 1, glucose transporter 1, asparagine synthetase and 1-acylglycerol-3-phosphate O-acyltransferase 1. These factors induce metabolic changes and regulate metabolic pathways together with major energy sources associated with mutant KRAS, and they are often overexpressed in CRC patients with poor prognosis ( 38 ). ACSL1 is involved in lipid synthesis, modification and β-oxidation; and SCD is the main enzyme controlling the rate of conversion of saturated FA to monounsaturated FA ( 39 ), which is crucial for cancer cells ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described an energy metabolism network link between KRAS-mutant CRC and multiple metabolism, including glycolysis associated with KRAS status alongside factors and metabolic genes. These metabolic genes and factors induce metabolic changes and regulate energy metabolic pathways together with major energy sources associated with mutant KRAS, often overexpressing in patients with poor prognosis of CRC [43]. It has shown that there is high level of glycolysis in the CRC cell line (HCT116).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming contributes to tumor development, metastasis and drug resistance. Therefore, others and we have proposed to exploit the metabolic liabilities to treat cancers [13,[37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%